2015
DOI: 10.1002/jmri.24838
|View full text |Cite
|
Sign up to set email alerts
|

Safety of gadoxetate disodium: Results from the clinical phase II–III development program and postmarketing surveillance

Abstract: Purpose: To summarize the safety data of gadoxetate disodium, reported in 12 Phase II and III clinical development studies and in the postmarketing surveillance database. Materials and Methods: Patients with liver lesions received gadoxetate disodium-enhanced liver magnetic resonance imaging (MRI). Adverse events (AEs) were recorded and evaluated with regard to a potential drug relationship. Subgroup analyses were run on patients with special medical history. Worldwide spontaneous AEs and adverse drug reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…However, no previous studies had been conducted to investigate and compare the AARs induced by these 2 contrast agents in a large population to support the presume, though there is no lack of surveillance studies performed to prove the safety and tolerability of iodinated contrast media. 37 …”
Section: Introductionmentioning
confidence: 99%
“…However, no previous studies had been conducted to investigate and compare the AARs induced by these 2 contrast agents in a large population to support the presume, though there is no lack of surveillance studies performed to prove the safety and tolerability of iodinated contrast media. 37 …”
Section: Introductionmentioning
confidence: 99%
“…This is in line with large safety reviews of both agents. Endrikat et al 20 reported 10.1% of AEs of which 4.1% were classified as related to gadoxetate disodium administration in an analysis of 12 clinical development studies, including 1989 patients. Likewise, Shellock et al 21 found 18% of AEs with 14% AEs considered related to gadobenate dimeglumine administration in a review of 79 clinical studies, including 2982 patients.…”
Section: Discussionmentioning
confidence: 99%
“…No further imaging was needed in the gadoxetate disodium group, and comparison of efficacy parameters demonstrated diagnostic superiority in the gadoxetate disodium enhanced MRI group (6). The excellent safety profile of gadoxetate disodium has been demonstrated in several clinical studies and in post-marketing experience (1,79). As of 30 April 2016, more than 3.6 million patients have been exposed to gadoxetate disodium worldwide since approval in March 2004.…”
Section: Introductionmentioning
confidence: 94%